Spatial Similarity Relations in Multi-scale Map Spaces - Yan, Haowen; Li, Jonathan (Springer International Publishing : Imprint: Springer, 2015)
How does one determine how similar two maps are? This book aims at the theory of spatial similarity relations and its application in automated map generalization, including the definitions, classification and features of spatial similarity relations. Included also are calculation models of spatial similarity relations between arbitrary individual objects and between arbitrary object groups, and the application of the theory in the automation of the algorithms and procedures in map generalization. .